1994
DOI: 10.1021/bi00174a041
|View full text |Cite
|
Sign up to set email alerts
|

17.beta.-(N-tert-Butylcarbamoyl)-4-aza-5.alpha.-androstan-1-en-3-one Is an Active Site-Directed Slow Time-Dependent Inhibitor of Human Steroid 5.alpha.-Reductase 1

Abstract: 17 beta-(N-tert-butylcarbamoyl)-4-aza-5 alpha-androstan-1-en-3-one (finasteride), which has been approved for treatment of benign prostatic hyperplasia, is shown here to be a slow time-dependent inhibitor of human steroid 5 alpha-reductase isozyme 1. This inhibition is characterized by an initial, fast step where the inhibitor binds to the enzyme followed by a slow step that leads to a final enzyme-inhibitor complex (EI*). No recovery of activity from this EI* complex was observed after dialysis for 3 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…The apparent K i for both finasteride and dutasteride in those experiments was calculated after transient expression of the reconstructed variant clones in mammalian cells followed by 10-min in vitro enzyme assays (Makridakis et al 2000(Makridakis et al , 2004. However, finasteride is a slow, time-dependent inhibitor of steroid 5 -reductase (Faller et al 1993, Tian et al 1994, 1995. Therefore, longer finasteride incubations with the wild-type enzyme are expected to result in better inhibition, or lower apparent K i (see e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparent K i for both finasteride and dutasteride in those experiments was calculated after transient expression of the reconstructed variant clones in mammalian cells followed by 10-min in vitro enzyme assays (Makridakis et al 2000(Makridakis et al , 2004. However, finasteride is a slow, time-dependent inhibitor of steroid 5 -reductase (Faller et al 1993, Tian et al 1994, 1995. Therefore, longer finasteride incubations with the wild-type enzyme are expected to result in better inhibition, or lower apparent K i (see e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Those results, however, were based on 10-min reactions, while finasteride is a slow, time-dependent inhibitor of steroid 5 -reductase (e.g. Faller et al 1993, Tian et al 1994. Thus, we reasoned that longer incubations with either inhibitor would be better approximations of the true inhibition in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although of interest in relation to alcoholism risk, the GABRA2 polymorphism that was examined in this study as a moderator of alcohol's effects has not been shown to be functional; the variation in this gene that underlies the association with alcohol dependence remains to be determined. Although finasteride is a potent antagonist of type 2 5AR, it has modest antagonist activity at type 1 5AR (Tian et al, 1994;Tian, 1996), the predominant isoform in the mature human brain (Poletti et al, 1998;Stoffel-Wagner et al, 1998). To compensate for the lower antagonist activity of finasteride at the human brain type 1 5AR, we administered a high dose of the drug (ie a total of 200 mg over 24 h, which is 40 times the standard daily dose).…”
Section: Subjective Effects Of Alcoholmentioning
confidence: 99%
“…Finastride, a synthetic antiandrogenic drug is marketed for Benign prostrate hyperplasia and androgenic alopecia and the mechanism involved is inhibition of 5α-reductase activity (Tian et al, 1994) Finasteride also has been used topically to treat androgenetic alopecia (Mazzarella et al, 1997). For the treatment of androgen related disorders like androgenetic alopecia, fi nasteride has been approved by USFDA (Libecco & Bergfeld, 2004), but there are many side effects associated with fi nasteride.…”
Section: Introductionmentioning
confidence: 99%